1988
DOI: 10.1055/s-2007-1024990
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maximal Physical Exercise on T-Lymphocyte Subpopulations and on Interleukin 1 (IL 1) and Interleukin 2 (IL 2) Production in Vitro

Abstract: Maximal physical exercise was performed on a Monark bicycle ergometer according to individual schemes. The investigations were carried out on 11 highly trained cyclists, aged 20 +/- 1 years. Heart rate (HR) amounting to about 200 bts/min and oxygen consumption stabilization were considered as criteria for maximal physical exercise. Lymphocyte phenotypes were determined using monoclonal antibodies. A significant increase in Ts (suppressor, cytotoxic) and a moderate increase in Th (helper, inducer) and NK (natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
2
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 6 publications
2
39
2
1
Order By: Relevance
“…These results are in accordance with studies by Drenth et al (1996) and Northo et al (1994), who found a decreased synthesis of these cytokines, not on a per cell basis, but for the whole blood. In contrast, other authors have described an elevated synthesis of IL-1b (Cannon et al 1991;Haahr et al 1991;Lewicki et al 1988) and an unimpaired (Haahr et al 1991) or higher (Cannon et al 1991) production of TNF-a. These contradictory results might be attributable to dierences in the intensity and duration of exercise.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…These results are in accordance with studies by Drenth et al (1996) and Northo et al (1994), who found a decreased synthesis of these cytokines, not on a per cell basis, but for the whole blood. In contrast, other authors have described an elevated synthesis of IL-1b (Cannon et al 1991;Haahr et al 1991;Lewicki et al 1988) and an unimpaired (Haahr et al 1991) or higher (Cannon et al 1991) production of TNF-a. These contradictory results might be attributable to dierences in the intensity and duration of exercise.…”
Section: Discussionmentioning
confidence: 77%
“…catecholamines and cortisol) on cytokine production. Several authors (Haahr et al 1991;Lewicki et al 1988;Northo et al 1994;Tvede et al 1993) have described a reduced phytohaemagglutinin (PHA)-stimulated interleukin (IL)-2 production in cell culture after exhaustive exercise. However, an increased synthesis (concanavalin-A-stimulated) has also been reported (Northo et al 1994).…”
Section: Introductionmentioning
confidence: 98%
“…The eect of high intensity exercise on T and B cell functional capacity is not clear. Data are available suggesting both unchanged (Nieman et al 1994(Nieman et al , 1995Nielsen et al 1996) and reduced lymphocyte proliferation capacity (Frisina et al 1994;Hinton et al 1997) or markers of lymphocyte activation (Lewicki et al 1988;Gray et al 1992) immediately after high intensity exercise. The con¯icting nature of the data precludes meaningful interpretation as to the eect of exercise on T and B lymphocyte function (Nielsen et al 1996).…”
Section: Introductionmentioning
confidence: 96%
“…In studies on lymphocyte subsets, a decreased ratio of T-helper to Tcytotoxic (CD4 : CD8) cells in athletes after acute exhaustive exercise observed by Berk et al, in 1986, has also been confirmed by Lewicki et al (1988) and Haq et al (1993). It has been suggested that a ratio of CD4 : CD8 cells below 1.5 is subnormal, and may be a cause of and an indicator of, immunosuppression (Nash, 1986;Keast et al, 1988;Shepherd et al, 1991).…”
Section: The Immune Response To Exhaustive Exercisementioning
confidence: 76%